Principles of Public Administration in Islamic Education: A Study of Q.S An-Nisa: 58 - Dwi Wulan Sari; Sinta Syamsuddin; Dea Sapitri (Wahana Islamika Jurnal Studi Keislaman, 2026)
The principle of trust contained in Q.S An-Nisa verse 58 is a direct command from Allah SWT that must always be upheld. Trust is not only about safeguarding the wealth that has been given, but also includes justice in establishing Allah SWT's law among humans. This study aims to examine the relevance of Q.S An-Nisa verse 58 in relation to public administration from the perspective of Islamic education. The research method used to obtain concrete results in this study was library research. Data sources were obtained from libraries, such as books, journals, databases, and other relevant information. The results of the study show that public administration has a strong relevance to Q.S. An-Nisa verse 58 in Islamic education. This verse emphasizes the principles of trustworthiness and justice as the ethical foundation of government administration and public service. In Islamic education, these values play an important role in shaping the character of state officials to be honest, accountable, and responsible. The integration of the values of Q.S. An-Nisa verse 58 in Islamic education, such as honesty, justice, trustworthiness, and responsibility, serves as a guideline for strengthening ethical governance and instilling awareness that public office is a trust that will one day be accounted for before Allah SWT.